Economic Feasibility of Stand-Alone Wind Energy Hybrid with Bioenergy from Anaerobic Digestion for Electrification of Remote Area of Pakistan - Raheem, Abdur; Hassan, Mohammad Yusri; Shakoor, Rabia; Rasheed, Nadia (International Journal of Integrated Engineering, 2015)
Hybrid Renewable Energy systems (HRES) are gaining importance throughout the world because of the finite sources of oil and gas reservoirs. These have the great ability in the production of electrical energy and cleaning the environment. It is difficult to get grid electricity in the remote areas where no infrastructure exists. The utilization of renewable sources is the ultimate solution for the generation of electricity. In this paper, the economic modeling of Hybrid system consisting of Wind/biomass is explored for the remote area ‘Jangiah’ of Balochistan province, Pakistan. Anaerobic Digestion of biomass is used to get biogas. This source is used to complement the uncertainties in the wind production. Homer is used to simulate the hybrid model. Economic analysis is performed to get the net present value (NPV) and cost of energy. It is observed that wind/biomass alone is capable to meet the demand of community which consumes 60 kW peak daily along with the storage backup. This system is the most economical with COE equal to 0.118 US$/kWh following the hybrid biomass/wind/diesel system with COE 0.202 US$/kWh. The sensitivity analysis is carried out and shows that the proposed system is sensitive to the prices of fossil fuel and project lifespan. The net present value increases as the lifetime of the project increases from 15 years to 30 years. It can also be concluded that if the price of the diesel drops below 0.8 US$/liter, the traditional system using fossil fuels will become the most suitable system for the generation of electricity in remote areas.